Hybrid Fault-Tolerant Control in Cooperative Robotics: Advances in Resilience and Scalability - Urrea-Onate, E (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Cooperative robotics relies on robust fault-tolerant control (FTC) to maintain resilience in dynamic environments, where actuators are pivotal to system reliability. This review synthesizes advancements in hybrid FTC, integrating mechanical redundancy with electronic adaptability and learning-based techniques like deep reinforcement learning and swarm-optimized control, drawing from interdisciplinary evidence across manufacturing, healthcare, agriculture, space exploration, and underwater robotics. It examines how these approaches enhance uptime, precision, and coordination in multi-robot systems, reporting significant improvements despite physical validation being limited to approximately one-quarter of strategies. Addressing gaps in prior work by overcoming limitations of traditional methods, it extends to Construction 5.0, supporting human–robot collaboration (HRC) through scalability and adaptability. Future efforts will prioritize broader testing, standardized benchmarks, safety considerations, and optimization under uncertainty to align theoretical gains with practical outcomes, enhancing resilient automation across domains. © 2025 by the author.
Keywords: cooperative robotics; fault-tolerant control; actuator redundancy; real-time adaptability; hybrid systems; bioinspired actuation; learning-based control; scalability; manufacturing automation; digital twins